Three transition-metal complexes with the macrocyclic ligand meso-5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane (L): [Cu(ClO4)2(L)], [Zn(NO3)2(L)] and [CuCl(L)(H2O)]Cl - Yasmin, Sabina (2013)
The three transition-metal complexes, (meso-5,7,7,12,14,14- hexamethyl-1,4,8,11-tetraazacyclotetradecane-4N)bis(perchlorato- O)copper(II), [Cu(ClO4)2(C18H40N4)], (I), (meso- 5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane- 4N)bis(nitrato-O)zinc(II), [Zn(NO3)2(C18H40N4)], (II), and aquachlorido(meso-5,7,7,12,14,14-hexamethyl-1,4,8,11- tetraazacyclotetradecane-4N)copper(II) chloride, [CuCl- (C18H40N4)(H2O)]Cl, (III), are described. The molecules display a very similarly distorted 4+2 octahedral environment for the cation [located at an inversion centre in (I) and (II)], defined by the macrocycle N4 group in the equatorial sites and two further ligands in trans-axial positions [two O? ClO3 ligands in (I), two O?NO2 ligands in (II) and one chloride and one aqua ligand in (III)]. The most significant difference in molecular shape resides in these axial ligands, the effect of which on the intra- and intermolecular hydrogen bonding is discussed. In the case of (I), all strong hydrogenbond donors are saturated in intramolecular interactions, while weak intermolecular C?H O contacts result in a three-dimensional network. In (II) and (III), instead, there are N?H and O?H donors left over for intermolecular interactions, giving rise to the formation of strongly linked but weakly interacting chains.